ANALISIS KEBUTUHAN INSTRUMEN PENILAIAN APRESIASI PUISI BERBASIS MODEL P-IKADKA DI SEKOLAH DASAR - Khairunnisa, Pathin Haifa; Seni Apriliya; Muhammad Rijal Wahid Muharram (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The research was motivated by the unavailability of special assessment instruments to assess poetry appreciation learning in elementary schools (SD). This research explores the need for poetry appreciation assessment instruments to draft an assessment instrument development product that can facilitate educators in assessing poetry appreciation learning in elementary schools. The research method used was the descriptive qualitative method. Data collection techniques were carried out using observations and interviews conducted from 26 February to 4 March 2024 with three grade IV elementary school educators in Tasikmalaya City. The data obtained were then analyzed using thematic analysis. The findings of this study, are: (1) the learning of poetry appreciation carried out has not included appreciation activities, namely understanding, responding to, and assessing poetry; (2) there are educators‘ misconceptions about the concept of poetry appreciation; (3) two educators have developed assessment instruments independently for learning poetry, but have not included students’ appreciation activities of poetry; (4) the assessment instruments developed have not been prepared based on a special learning model for literature appreciation. Based on this, there is a need to develop a poetry appreciation assessment instrument based on a literary appreciation learning model to holistically measure students' understanding, response, and poetry assessment.